Stress corrosion cracking of AISI 304 under chromium variation within the standard limits: Failure analysis implementing microcapillary method. (December 2022) - Yazdanpanah, Arshad; Pezzato, Luca; Dabalà, Manuele
Highlights: High SCC susceptibility of low Cr alloy despite having sufficient Cr accepted by standard limits. SCC length was highly dependent on Cr content in boiling MgCl2 solution. Significant dependency of electrochemical behaviour to Cr content within standard limits. Considerable correlation between tensile straining and Cr content with SCC susceptibility. Secondary intergranular cracks were observed on the fracture surface for the low Cr case. Abstract: This study focuses on the failure analysis of an industrial part made of AISI 304 that severely ruptured, while another identical part operated under identical service conditions has no sign of fracture. Various electrochemical polarization responses and stress corrosion cracking (SCC) susceptibility were compared by employing the microcapillary method on representative samples. The dominant factor was identified to be the chromium (Cr) content variation within the range of standard designations. Various concentration levels of sodium chloride aqueous solution were studied for both strained and unstrained conditions. Results highlighted higher susceptibility to pitting and SCC for the specimens with lower Cr content, indicating a more severe condition at higher chloride concentrations.